Penerapan Kartu Kuartet sebagai Media Pembelajaran Perilaku Hidup Bersih Siswa Sekolah Dasar di Samarinda - Zahrah Nuriah Ramah; Dwi Hendriani; Bernadetha Bernadetha (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Clean and Healthy Living Behavior (PHBS) refers to an initiative aimed at motivating communities to take an active role as agents of change in enhancing overall health quality. However, PHBS implementation in schools remains low. This study examines the impact of health education using quartet card games on PHBS behavior among students at SDN 010 Loa Janan Ilir. This study employed a quantitative method with a quasi-experimental design using a non-equivalent control group pretest-posttest approach. It included 74 fifth-grade students from SDN 010 Loa Janan Ilir, divided evenly into two groups—intervention and control—with 37 participants in each. Total sampling was used for participant selection. Univariate analysis revealed significant increases in knowledge (83.3%), attitudes (91.7%), and actions (58.3%) in the intervention group after the pretest and posttest, compared to increases in knowledge (8.3%), attitudes (8.3%), and actions (63.9%) in the control group. The bivariate analysis revealed statistically significant impacts on knowledge, attitudes, and behaviors within the intervention group (p-value = 0.000), indicating that quartet card games significantly influenced PHBS behavior implementation. The use of the quartet card game positively impacted the knowledge, attitudes, and behaviors of students regarding hygiene and health-oriented lifestyles at elementary school in Samarinda.